Deimplementation of Routine Chest X‐rays in Adult Intensive Care Units. Issue 2 (1st February 2019) - Trumbo, Silas P; Iams, Wade T; Limper, Heather M; Goggins, Kathryn; Gibson, Jayme; Oliver, Lauren; Leverenz, David L; Samuels, Lauren R; Brady, Donald W; Kripalani, Sunil
Abstract : BACKGROUND: Choosing Wisely ® is a national initiative to deimplement or reduce low‐value care. However, there is limited evidence on the effectiveness of strategies to influence ordering patterns. OBJECTIVE: We aimed to describe the effectiveness of an intervention to reduce daily chest X‐ray (CXR) ordering in two intensive care units (ICUs) and evaluate deimplementation strategies. DESIGN: We conducted a prospective, nonrandomized study with control data from a historical period. Qualitative evaluation was guided by the Consolidated Framework for Implementation Research. SETTING: The study was performed in the medical intensive care unit (MICU) and cardiovascular intensive care unit (CVICU) of an academic medical center in the United States from October 2015 to June 2016. PARTICIPANTS: The initiative included the staff of the MICU and CVICU (physicians, surgeons, nurse practitioners, fellows, residents, medical students, and X‐ray technologists). INTERVENTION COMPONENTS: We utilized provider education, peer champions, and weekly data feedback of CXR ordering rates. MEASUREMENTS: We analyzed the CXR ordering rates and factors facilitating or inhibiting deimplementation. RESULTS: Segmented linear time‐series analysis suggested a small but statistically significant decrease in CXR ordering rates in the CVICU ( P < .001) but not in the MICU. Facilitators of deimplementation, which were more prominent in the CVICU, included engagement of peer champions, stable staffing, and regular data feedback. Barriers included the need to establish goal CXR ordering rates, insufficient intervention visibility, and waning investment among medical residents in the MICU due to frequent rotation and competing priorities. CONCLUSIONS: Intervention modestly reduced CXRs ordered in one of two ICUs evaluated. Understanding why adoption differed between the two units may inform future interventions to deimplement low‐value diagnostic tests. Abstract :